2019
DOI: 10.7759/cureus.5247
|View full text |Cite
|
Sign up to set email alerts
|

Primary Spinal Astrocytomas: A Literature Review

Abstract: Primary spinal astrocytoma is a subtype of glioma, the most common spinal cord tumor found in the intradural intramedullary compartment. Spinal astrocytomas account for 6-8% of all spinal cord tumors and are primarily low grade (World Health Organization grade I (WHO I) or WHO II). They are seen in both the adult and pediatric population with the most common presenting symptoms being back pain, sensory dysfunction, or motor dysfunction. Magnetic Resonance Imaging (MRI) with and without gadolinium is the imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 39 publications
0
40
0
8
Order By: Relevance
“…Also, our data revealed that the lower expression of miR-1225-5p indicated the shorter survival time of patients. Recently, it has been found that in primary spinal astrocytoma (a subtype of gliomas), the most significant factors associated with poor prognosis are the lesions with older age and higher histological grade at the initial diagnosis [ 26 ]. On the basis of references and the results of this study, we considered that miR-1225-5p is a biomarker for diagnosis and treatment of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our data revealed that the lower expression of miR-1225-5p indicated the shorter survival time of patients. Recently, it has been found that in primary spinal astrocytoma (a subtype of gliomas), the most significant factors associated with poor prognosis are the lesions with older age and higher histological grade at the initial diagnosis [ 26 ]. On the basis of references and the results of this study, we considered that miR-1225-5p is a biomarker for diagnosis and treatment of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi aucun patient de notre série n´a bénéficié d´un traitement complémentaire même lorsqu´il y avait une indication (cas du plasmocytome). Plusieurs auteurs [ 10 , 14 , 17 , 18 ] avaient réalisé une chimiothérapie anticancéreuse dans les cas de myélome multiple, de plasmocytome, de sarcome granulocytaire, de neuroblastome. D´autres auteurs [ 10 , 19 ] pratiquaient une radiothérapie dans les cas de plasmocytome solitaire osseux et de neurofibrosarcome primitif.…”
Section: Discussionunclassified
“…The study was a retrospective multicentric analysis conducted in 5 neurosurgical high-volume centers in Germany (3), Austria (1), and Switzerland (1). We analyzed relevant details on the type of surgery performed, the neurosurgical approach, preoperative clinical state (modified McCormick grading), early and long-term postoperative neurological function, tumor size and histopathological results (including the WHO grading of the tumor, molecular markers such as Ki-67, MGMT, and IDH-1 mutation), the EOR (gross total resection [GTR] defined as a complete removal of contrast enhancing tumor, subtotal resection [STR] defined as a removal of more than 90% of the contrast enhancing tumor, tumor debulking, or biopsy), and time to tumor recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its rareness, data on adjuvant therapy such as combined chemo-and radiotherapy are sparse [13][14][15], and decisions on a patient's optimal treatment are taken individually without defined guidelines. While most intramedullary astrocytomas of the spinal cord are low-grade tumors (World Health Organization WHO I or II tumors) [1,16], studies on spinal highgrade gliomas are missing. In our study, we therefore analyzed the surgical approach and clinical outcome of patients suffering from infiltrating astrocytomas WHO II, III, and IV in order to better understand the influence of the surgical approach and adjuvant treatment on the overall survival (OS) and tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation